Memoria reflexiva de un músico-instrumentista, bailarín y formador, fundador de la Corporación Cultural Semillas en Acacias- Meta (2024)
The present investigation consists of analysis and interpretation of the artistic and pedagogical experience of master Nelson Yesid Gil Soriano. This document is the result of a systematization of the teacher’s life and career, which is divided into three phases: musical training, dance training, and student training. Through this, the creation of the Semillas Cultural Corporation, in which training processes for dance and music groups are carried out, who are part of different cultural folkloric events at the national level